Management of organizational change in Chilean companies - Raineri B., Andrés (Estudios de Administración, 2001)
Globalization has brought an intensification of competition throughout most of the world. These new winds of competition have brought threats to local companies in the forms of new entrants in their markets, new technologies, and regulatory shifts. All these changes have pressed local companies to either adapt to the new reality or disappear from the market. An extensive literature has been developed of how organizations should better cope with change. Literature on organizational change is frequently suggesting the use a set of "behavioral practices" that should help in the management of change processes and the administration of resistances from within the organization (Kanter, Stein, y Jick, 1992; Dauphinais y Pederson, 1995; Nadler, 1998). The use of these practices should help firms be more flexible and adaptive to environmental threats. This paper, which is exploratory and descriptive in nature, compares the use of such practices within and between firms varying in their size, as measured by number of employees. Results showed that some practices were used more frequently than others. In particular, practices related to the preparation for change were more frequently used than change implementation practices. It was also observed that larger firms, in comparison to smaller firms, used in a greater proportion change management practices. These relations could be better explained when it was demonstrated that these differences are originated specifically in the larger use that big companies have of practices related to preparing for the change process (diagnosis, strategic planning, et cetera). Several possible arguments are discussed in an attempt to explain the findings.